How to inhibit transforming growth factor beta safely in diabetic kidney disease. Issue 1 (January 2021) - Yang, Yuxin; Shi, Kexin; Patel, Devang M.; Liu, Fang; Wu, Tieqiao; Chai, Zhonglin
Abstract : Purpose of review: Diabetic kidney disease (DKD) is a leading cause of mortality and morbidity in diabetes. This review aims to discuss the major features of DKD, to identify the difficult barrier encountered in developing a therapeutic strategy and to provide a potentially superior novel approach to retard DKD. Recent findings: Renal inflammation and fibrosis are prominent features of DKD. Transforming growth factor beta (TGFβ) with its activity enhanced in DKD plays a key pathological profibrotic role in promoting renal fibrosis. However, TGFβ is a difficult drug target because it has multiple important physiological functions, such as immunomodulation. These physiological functions of TGFβ can be interrupted as a result of complete blockade of the TGFβ pathway if TGFβ is directly targeted, leading to catastrophic side-effects, such as fulminant inflammation. Cell division autoantigen 1 (CDA1) is recently identified as an enhancer of profibrotic TGFβ signaling and inhibitor of anti-inflammatory SIRT1. Renal CDA1 expression is elevated in human DKD as well as in rodent models of DKD. Targeting CDA1, by either genetic approach or pharmacological approach in mice, leads to concurrent attenuation of renal fibrosis and inflammation without any deleterious effects observed. Summary: Targeting CDA1, instead of directly targeting TGFβ, represents a superior approach to retard DKD.